INDEPENDENSI, PROFESIONALISME, DAN SKEPTISME PROFESIONAL AUDITOR SEBAGAI PREDIKTOR KETEPATAN PEMBERIAN OPINI AUDITOR OLEH AKUNTAN PUBLIK - Ari Prasetya, I Wayan (E-Jurnal Akuntansi; Vol 9 No 2 (2014), 2014)
In the current era of globalization such as the need for financial statements should have predictive value in order to provide relevant information for its users. The financial report is a tool that is held accountable to the company's management of its resources. One of the measures taken by the company is to audit the financial statements using the services of a third party that is a public accountant. The purpose of this study was to determine the effect of independence, professionalism, and professional skepticism of auditors to the accuracy of the provision of public opinion by the accountant. This study used a public accounting firm in the area of Bali with 59 observations were obtained by purposive sampling method. Research results show that variable independence, professionalism, and professional skepticism of auditors positive and significant effect on the accuracy of giving opinions.
Keywords: Purposive sampling, Independence, Professionalism, Skeptisme professional, audit opinion